Effect of tailored, daily feedback with lifestyle self‐monitoring on weight loss: The SMARTER randomized clinical trial. Issue 1 (12th December 2021) - Burke, Lora E.; Sereika, Susan M.; Parmanto, Bambang; Bizhanova, Zhadyra; Kariuki, Jacob K.; Cheng, Jessica; Beatrice, Britney; Loar, India; Pulantara, I Wayan; Wang, Yuhan; Cedillo, Maribel; Conroy, Molly B
Abstract: Objective: This study aimed to test the efficacy of self‐monitoring and feedback (SM+FB) versus SM without FB (SM) in a behavioral weight‐loss intervention at 6 months. Methods: This was a randomized clinical trial. Eligibility criteria included the following: ≥18 years of age, BMI ≥ 27 and ≤43, smartphone user, and ability to engage in moderate physical activity. All participants received a 90‐minute 1:1 counseling session, a Fitbit Charge 2, and a digital scale for SM. SM+FB participants were provided access to a customized smartphone application that provided three daily FB messages. The primary outcome was percentage of weight change from 0 to 6 months. Results: The sample ( N = 502) was 45 (SD 14.4) years old, BMI was 33.7 (SD 4.00) kg/m 2, 79.5% of participants were female ( n = 399), and 84.3% were White ( n = 423). At 6 months, there was 85.86% retention and a significant percentage of weight change in both groups (SM+FB: −3.16%, 95% CI: −3.85% to −2.47%, p < 0.0001; SM: −3.20%, 95% CI: −3.86% to −2.54%, p < 0.0001) but no significant between‐group mean difference (−0.04%, 95% CI: −0.99% to 0.91%, p = 0.940). A ≥5% weight loss was achieved by 31.9% of the SM+FB group and 28.3% of the SM group. Conclusions: There was no significant between‐group difference in weight loss at 6 months.